Design and Validation of a Microarray for Detection, Hemagglutinin Subtyping, and Pathotyping of Avian Influenza Viruses - Gall, Astrid (American Society for Microbiology (ASM), 2009)
Continuing threats of devastating outbreaks in poultry and of human infections caused by highly pathogenic avian influenza virus (HPAIV) H5N1 emphasize the need for the further development of rapid and reliable methods of virus detection and characterization. Here we report on the design and comprehensive validation of a low-density microarray as a diagnostic tool for the detection and typing of avian influenza virus (AIV). The array consists of one probe for the conserved matrix gene and 97 probes targeting the HA(0) cleavage-site region. Following fragment amplification by a generic PCR approach, the array enables AIV detection, hemagglutinin (HA) subtyping, and pathotyping within a single assay. For validation, a panel of 92 influenza A viruses which included 43 reference strains representing all 16 HA subtypes was used. All reference strains were correctly typed with respect to their HA subtypes and pathotypes, including HPAIV H5N1/Asia, which caused outbreaks in Germany in 2006 and 2007. In addition, differentiation of strains of the Eurasian and North American lineages of the H5 and H7 subtypes was possible. The sensitivity of the microarray for the matrix gene is comparable to that of real-time reverse transcription-PCR (RT-PCR). It is, however, 10- to 100-fold lower than that of real-time RT-PCR with respect to HA subtyping and pathotyping. The specificity of the array was excellent, as no pathogens relevant for differential diagnosis yielded a positive reaction. Validation with field samples included 19 cloacal swab specimens from wild and domestic birds. Influenza A virus was verified in all samples, whereas the HA subtypes could be determined for 14 samples. The results demonstrate that the microarray assay described complements current methods and can accelerate the diagnosis and characterization of AIV.